2015
DOI: 10.1021/es5048792
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Nematodes Affect Selenium Bioaccumulation, Oxidative Stress Biomarkers, and Health Parameters in Juvenile Rainbow Trout (Oncorhynchus mykiss)

Abstract: In environmental studies, parasites are often seen as a product of enhanced host susceptibility due to exposure to one or several stressors, whereas potential consequences of infections on host responses are often overlooked. Therefore, the present study focused on effects of parasitism on bioaccumulation of selenium (Se) in rainbow trout (Oncorhynchus mykiss). Joint effects of biological (parasite) and chemical (Se) stressors on biomarkers of oxidative stress (glutathione-S-transferase (GST), superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
0
16
0
1
Order By: Relevance
“…Some other studies (Sures et al 1999a;Sures 2002) pointed out that the competition for minerals may lead to extra absorption of non-essential elements such as toxic lead and cadmium due to their similarity in chemical properties. This extra absorption of toxic metals from host tissues has occasionally been interpreted as a "beneficial aspect" of parasitism (Sures and Siddall, 1999;Turčeková et al, 2002;Eira et al, 2009;Hursky and Pietrock, 2015). However, no ecoparasitological studies dealing with relationships between heavymetal concentrations in different parasite species within the helminth infrapopulation in the host' intestine was done.…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies (Sures et al 1999a;Sures 2002) pointed out that the competition for minerals may lead to extra absorption of non-essential elements such as toxic lead and cadmium due to their similarity in chemical properties. This extra absorption of toxic metals from host tissues has occasionally been interpreted as a "beneficial aspect" of parasitism (Sures and Siddall, 1999;Turčeková et al, 2002;Eira et al, 2009;Hursky and Pietrock, 2015). However, no ecoparasitological studies dealing with relationships between heavymetal concentrations in different parasite species within the helminth infrapopulation in the host' intestine was done.…”
Section: Introductionmentioning
confidence: 99%
“…This might account for the less unequal partitioning of Fe, Cu, and Zn in the chub-acanthocephalan system. The lower concentration of Se in the nematode Raphidascaris acus compared to the concentration in the trout Oncorhynchus mykiss as found by Hursky and Pietrock [85] might be related to the limited induction of bile acids due to the low concentration of Se in the investigated trout. In particular, the concentration of Se in the trout investigated in the study of Hursky and Pietrock [85] was lower than the concentration of Se in the muscle of the bream in the study of Mazhar et al [87] by more than one order of magnitude.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, Genc et al [96] demonstrated that the accumulation of Cd, Cr, Cu, Fe, Hg, Mn, Pb and Zn in the European eel Anguilla anguilla infected with the nematode Anguillicola crassus was not significantly different from that in the uninfected eel. By contrast, infection with parasites has been reported to reduce the concentration of metals accumulated in the fish host in many of previous studies [18,20,85,97]. Sures and Siddall [18] and Sures et al [20] reported lower concentrations of Pb in the chub infected with the acanthocephalan P .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations